Enhanced Recovery in Surgical Intensive Care: A Review - Jovanović, Gordana; Jakovljević, Dea Karaba; Lukić-Šarkanović, Mirka (Frontiers in Medicine, 2018)
A patient can be admitted to the intensive care unit and after an emergency or elective surgery. In case of admission after elective surgery, there is a need for further support, or the patient having coexisting comorbidities. In theory, the implementation of the ERAS protocols in surgery should decrease the need for ICU beds, but we could not eradicate all complications after surgery, so some patients will inevitably develop some postoperative complications. The next question is what we can do for our surgical patients in ICU to further enhance their recovery? To promote early enhanced recovery in surgical intensive care - SICU, we should provide protocols for sedation and analgesia in the SICU (or develop local ones), implement tools for assessing the patient level of sedation and pain, develop and implement prevention and treatment strategies for postoperative delirium. The best practice will be to develop and implement care bundles for sedation, analgesia, and postoperative delirium in each SICU. AS for pain, agitation, and delirium, screening (measuring) for malnutrition is of great importance and should start preoperatively. Care bundles for early nutritional interventions and implementation of nutritional protocols should be developed by ICU teams. ERAS protocols encourage early mobilization of the patients of surgical critically ill patient even if on mechanical ventilation. Early mobilization is possible and should be implemented by special multidisciplinary ICU team. All team members must be familiar with protocols and implement them in their field of expertise. Personal and professional attitudes are critical for implementation. In the core of all our efforts should be the patient and his well-being.